2013
DOI: 10.1001/2013.jamaneurol.393
|View full text |Cite
|
Sign up to set email alerts
|

Progranulin Mutations as Risk Factors for Alzheimer Disease

Abstract: Importance: Mutations in the progranulin gene are known to cause diverse clinical syndromes, all attributed to frontotemporal lobar degeneration. We describe 2 patients with progranulin gene mutations and evidence of Alzheimer disease (AD) pathology. We also conducted a literature review.Observations: This study focused on case reports of 2 unrelated patients with progranulin mutations at the University of California, San Francisco, Memory and Aging Center. One patient presented at age 65 years with a clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 118 publications
(85 citation statements)
references
References 37 publications
3
78
0
4
Order By: Relevance
“…30 Similarly, at least one neuropathologically proven AD case was found to harbor a loss-offunction variant of GRN. 31 Apparently consistent with the hypothesis of several genes causing different dementing disorders, Guerreiro et al 32 reported a CADASIL-causing variant of the NOTCH3 gene in a family clinically diagnosed with AD. However, no evidence of an AD pathophysiological process was available, segregation analysis could not be interpreted, co-occurrence of two distinct diseases could not be excluded as consanguinity was observed and a recessive cause of AD-like dementia remained possible.…”
Section: Discussionmentioning
confidence: 72%
“…30 Similarly, at least one neuropathologically proven AD case was found to harbor a loss-offunction variant of GRN. 31 Apparently consistent with the hypothesis of several genes causing different dementing disorders, Guerreiro et al 32 reported a CADASIL-causing variant of the NOTCH3 gene in a family clinically diagnosed with AD. However, no evidence of an AD pathophysiological process was available, segregation analysis could not be interpreted, co-occurrence of two distinct diseases could not be excluded as consanguinity was observed and a recessive cause of AD-like dementia remained possible.…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, loss‐of‐function mutations in the progranulin gene are risk factors for developing AD as well as other neurodegenerative disorders 4, 6, 8. Together these findings suggest that progranulin plays a primarily neuroprotective role, reactively modifying or guarding against neurodegenerative processes.…”
Section: Discussionmentioning
confidence: 94%
“…In the CNS, progranulin expression increases with age in both neurons and microglia, and plays a role in neurite outgrowth, synapse modification, and the prevention of neuronal apoptosis 1, 2, 3, 4. This neuroprotective function is highlighted by the relationship between progranulin and neurodegenerative disease; heterozygous loss‐of‐function mutations in the gene encoding progranulin ( GRN ) cause frontotemporal dementia (FTD),5, 6 and a common rs5848 allele in the 3′UTR of GRN has been associated with both decreased serum and brain progranulin expression levels and increased risk of developing Alzheimer's disease (AD) 7, 8, 9. Additionally, misregulation of progranulin expression has been implicated in parkinsonism, neuronal ceroid lipofuscinosis, and other neuropsychiatric disorders 10, 11…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGRN is of particular interest in the context of neurodegenerative disease because its haploinsufficiency causes frontotemporal dementia in humans (59,60), and putative roles for PGRN in AD have been proposed (61). Interestingly, it was recently reported (based on genetic perturbations) that microglial PGRN limits amyloid plaque deposition in a mouse AD model (31).…”
Section: Discussionmentioning
confidence: 99%